Dexamethasone as adjuvant treatment in patients with acute severe pharyngitis : a descriptive study at Welcare Hospital emergency unit, Dubai, United Arab Emirates - Ishtayeh, Bilal (Stellenbosch : Stellenbosch University, 2016)
Thesis (MFamMed)--Stellenbosch University, 2015.